Less is beautiful : 69 stories of how 'less' succeeds in business - Kortleven, Cyriel, ....- (S.l. : Cyriel Kortleven, 2013)
'Less is Beautiful' is about being more effective with less. Get inspired by stories from various organisations that have implemented the 'Less is Beautiful' philosophy. Less is Beautiful is based upon 4 pillars: + Why more is too much + Start to stop + Simplify + Letting go This book is written for professionals who operate in business and/or governments and who are looking for ways to gain more results with less effort. You will find a broad spectrum of tools & examples ranging from famous companies such as Google and Apple, which are known for their simple principles, to an unusual social media campaign from Harry Potter's theme park; or going from the NYC 311 call center to patient-centered hospitals; or tools like the Aunt Bertha test to totally new concepts like nearling or wonder walk. Short stories, great practical insights and tips make this book unique. Enjoy the inspiration!